“Satan Made Him Do It!” The Development of a Satan Figure as Social-Theological Diagnostic Strategy from the late Persian Imperial Era to Early Christianity - Louis Cloete Jonker (Old Testament Essays, 2017)
The purpose of this article is, first of all, to provide a short overview of the socio-religious development to personalize evil into a Satan figure alongside God. Thereafter, I will provide one biblical example which stands at the beginning of this development, namely 1 Chronicles 21. This text analysis will merely serve as one example to illustrate the relationship between the socio-religious developments in the Second Temple period and biblical textual formation through the reinterpretation of earlier traditions. In a last section, I will reflect on how our awareness of this relationship between socio-religious development and reinterpretation impacts on how Christian theology participates in social-theological diagnostics today.